Case study of smoke and heat control systems in high-rise buildings - Căruntu Alexandru-Sorin; Teodosiu Cătălin-Ioan (E3S Web of Conferences)
New European technical regulations impose the need for Computational Fluid Dynamics (CFD) modeling of smoke and heat control systems for buildings with a height greater than 60 m. Consequently, this study presents CFD simulations in this context, focusing on two essential constructive elements in ensuring a safe evacuation of users from high-rise buildings, interconnected with each other: the smoke enclosure and the stairwell. It is worthwhile to mention that the developed numerical model considered requirements of technical regulations in force and data from specialized literature, as well as non-conformities of some constructive elements with fire protection roles. The results show the importance of all constructive elements with active and passive protection roles in case of fire. These elements contribute to reducing the effects produced by fires, especially in the case of non-conformities of the smoke and heat control systems, respectively of the smoke barriers (smokeproof enclosure access and exit fire doors).